Polymorphic microsatellite markers in the long-spined sea urchin Diadema setosum - Wang, Mingling; Li, Zhe; Ganmanee, Monthon; Xie, James Y.; Urriago, Juan Diego; Qiu, Jian Wen (My University, 2014)
We developed twenty polymorphic microsatellite markers for the long-spined sea urchin Diadema setosum by screening microsatellite enriched library, and characterized their polymorphism using two populations of 45 individuals. The number of alleles per locus ranged from 4 to 17, and the observed and expected heterozygosity varied from 0.0714 to 1.000 and 0.6655 to 0.9321, respectively. Twelve loci conformed to the Hardy–Weinberg equilibrium after Bonferroni correction. These polymorphic microsatellite markers will facilitate studies of population genetics and connectivity in D. setosum.
Keywords: Diadema; Microsatellite markers; Polymorphism; Sea urchin